Povidone Iodine Intrarectal Cleaning versus Formalin Needle Disinfection for Minimizing Transrectal Prostate Biopsy-related Infections (Bangladesh Journal of Urology, 2023)
Background: A most feared complication of transrectal prostate biopsy is post-biopsy infection and/or sepsis. Safe intraprocedural measures that complement the antibiotic prophylaxis are intrarectal povidone iodine instillation or formalin needle disinfection after every core of the biopsy. Both are more effective at preventing post-biopsy infection than performing antibiotic prophylaxis alone.Objective: To assess the effectiveness of povidone-iodine intrarectal cleaning and formalin needle disinfection to prevent infection after prostate biopsy.Methodology: This study was conducted from July 2021 to June 2022 with 90 patients who underwent prostate biopsy at NIKDU. Patients were randomized into 2 equal groups, 45 in each group, by lottery. Two groups were Group-F: Standard biopsy, where the needle is disinfected with 10% formalin after each core, and Group-P: intrarectal luminal instillation of 10 ml 10% povidone-iodine for 10 min before the biopsy. Endpoint of the study was the development of signs and symptoms of infection within 7 days of prostate biopsy.Result: In terms of age, S. PSA & prostate volume, there was no significant difference between the two group. Infective complications within 7 days of the prostate biopsy were observed in 14 patients (15.6%), 3.67 times more in Group-F patients (p=0.03), and a higher incidence of UTI (72.73%) was observed in Group-F (p=0.03) than Group- P patients. The incidence of septicemia, epididymal-orchitis, and acute prostatitis was not statistically significant between the two groups. E. coli was the predominant organism found on urine culture, followed by Klebsiella pneumoniae, Enterococcus faecalis, and proteus species.Conclusion: Along with prophylactic antibiotics, povidone iodine intrarectal cleaning is superior to formalin needle disinfection in preventing infective complications of prostate biopsy.Bangladesh J. Urol. 2022; 25(2): 80-83